IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN SMP NEGERI 2 KOLAKA - Nursyalim, Nursyalim; Ondeng, Syarifuddin; Saat, Sulaiman; Hanafi, Muh. Sain (Program Pascasarjana, UIN Alauddin Makassar, 2019)
This paper discusses the implementation of Islamic religious education learning in SMP Negeri 2 Kolaka. This research is a qualitative research field. To obtain data in this study, researchers dug through several data sources, such as school principals, vice principals, Islamic religious education teachers and students' parents, and non-Islamic religious education teachers, religious leaders, educational leaders of community leaders, using the observation method interviews, and documentation. The results showed that the implementation of Islamic Religious Education learning in schools had been going well, especially in implementing Islamic religious education learning and religious activities in schools. However, the role of teachers, especially non-Islamic education teachers in religious activities, is still less involved in religious activities. Therefore, it is better for Islamic religious education teachers to be more proactive towards non-Islamic religious education teachers to be more active so that religious activities become a shared responsibility. And in the implementation of learning using learning methods to make it easier for students to understand the subject matter through the habituation method, the exemplary method, the lecture method, the question and answer method, the story method, the assignment method, the demonstration method method, the group work method, the discussion method, the practice method, and many other learning methods.